Developing a preservation policy and procedure statement for a health sciences library. - Paulson, B A (1989)
The preconditions for creating a preservation policy document in a health sciences library are an existing preservation policy for the institution of which it is a part and administrative support for preservation. The assumption underlying preservation activity, from the formulation of general guidelines to the detail of operating procedure, is that collection development and preservation are complementary functions. Documentation of operational procedures in some detail should be a part of the statement. Since preservation activity cuts across functional library structures, all management staff should be involved in the planning process and be made aware of their responsibilities. The creation of a preservation policy statement will highlight unaddressed issues, procedural inadequacies, and differences in staff perceptions of priorities, but a written statement provides a framework for setting priorities and making decisions.